2021
DOI: 10.5455/msm.2021.33.288-292
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological Characteristics of Autoimmune Thyroiditis in the Tuzla Canton in the Period from 2015 to 2020

Abstract: Background: Bosnia and Herzegovina (B&H) is one of the countries of Southeast Europe with the lack of data about chronic autoimmune thyroid diseases (CAITD) epidemiology. Objective: This research aimed to assess incidence of CAITD in the Tuzla Canton of B&H during a 6-year period (2015–2020). Methods: We retrospectively evaluated 82,000 hospital records of inpatients and outpatients with possible thyroid symptoms residing in Tuzla Canton of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The total incidence of AITD per 100,000 of the population of TC in the six-year observed period was: in women 123.74, 95% CI; in men 16.25, 95% CI, or a total of 71.25, 95% CI. The highest recorded incidence was in women in 2017 (183.93/10 5 ) ( 17 ). Our results showed that the highest total incidence in Lukavac was recorded in 2017, and was 99.49, 95% CI, in which women were predominant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total incidence of AITD per 100,000 of the population of TC in the six-year observed period was: in women 123.74, 95% CI; in men 16.25, 95% CI, or a total of 71.25, 95% CI. The highest recorded incidence was in women in 2017 (183.93/10 5 ) ( 17 ). Our results showed that the highest total incidence in Lukavac was recorded in 2017, and was 99.49, 95% CI, in which women were predominant.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis was conducted of the medical records of 82000 patients at the Thyroid Diseases Department of the Radiology and Nuclear Medicine Clinic, of the University Clinical Centre (UCC) in Tuzla, B&H. The inclusion/exclusion criteria in the study were the same as in our previous study ( 17 ). People included in the study were patients older than 14 years, of both gender, with all forms of clearly defined AITD, living in the area of Lukavac, and in whom the disorder was diagnosed in the period from January 2015 to December 2020.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation